Design Of “Our Market” Sales Information System In The Web-Based Dringu Traditional Market - Yulianto, Yahya; Dyah Ariyanti; Rahma, Ary Analisa (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
As technology  advances  and  people's  needs for  shopping,  considering  that  currently  shopping  can  be  accessed through applications. The Probolinggo District Office of Industry and Trade facilitates buying and selling without entering the market, shopping online through the WhattsApp and Instagram applications with the "Mak Blonjo" icon, the Dringu traditional market is the program's main pilot project, the lack of informationabout products is an obstacle in marketing. The aim of this research is to produce an application in the form of a website with the "Our  Market"  icon  which  is  used  as  a  sales  information  system  in  the  Dringu  traditional  market  so  that it  can make  it  easier  for  various  parties  to  carry  out  fast  and  precise  interactions  and  transactions.  The  software development method uses the waterfall method. The system created uses the PHP programming language with the CodeIgniter framework and MYSQL database. System testing is carried out using the black box testing method. While  testing  the  satisfaction  of  the  application  uses  the  UAT  (user  acceptance  test)  test  in  the  form  of  a questionnaire and performs a Likert scale calculation. It can be concluded that the level ofsatisfaction with users of  the  web-based  "Pasar  Kita"  sales  application  reached  84.1%  with  15  consumer  respondents,  73.1%  with  3 admin/market clerk respondents and 76.1% with 15 merchant respondents. The final result of this research is that the website-based “Pasar Kita” sales information system design can be implemented in Dringu traditional markets as a form of ordering process service.